Environmental intervention as a tool for control of schistosomiasis: suggestions from a field study in Northeast Brazil Controle da esquistossomose mediante emprego de medidas ambientais: sugestões a partir de um estudo de campo no nordeste brasileiro - Kurt Kloetzel; Pedro Paulo Chieffi; Flair José Carrilho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
The present survey from the State of Alagoas (Brazil) emphasized, once again, the importance of peridomestic or neighbourhood foci in the transmission of schistosomiasis mansoni. Although the study area consisted of a compact and densely populated urban community (Bairro Frio, União dos Palmares county), prevalence as well as the distribution of high egg counts was quite patchy, exhibiting a spatial pattern correlated with the distribution of ditches and other small-sized collections of surface water. Despite the availability of satisfactory water supply in most households, as well as the absence of any major body of water capable of furthering transmission, egg counts in Bairro Frio exceeded any other in our previous experience. Morbidity, however, appeared to be insignificant, a trend which has been observed over the last decade in several other highly endemic areas. It appears clear to the authors that the control of transmission requires investment in environmental intervention and that this proposal, far from being utopic, can be furthered by quite modest means and through the participation of community or neighbourhood groups. O presente estudo, realizado no Estado de Alagoas, mais uma vez demonstrou o papel relevante dos focos peridomiciliares ou de vizinhança na transmissão da esquistossomose. Embora se trate de uma área urbana, compacta e densamente povoada (Bairro Frio, município de União dos Palmares), a distribuição tanto da prevalência como dos indivíduos com contagem de ovos elevada nas fezes obedeceu a nítido padrão espacial, altamente correlacionado com a distribuição de valetas de drenagem e outras pequenas coleções de água. Embora a maioria dos habitantes tenha acesso a água potável e, não obstante a ausência de coleções de água de algum vulto, capazes de manter a transmissão, a intensidade das contagens de ovos superou quaisquer dados anteriormente obtidos em outras áreas. Ainda assim, a morbidade mostrou-se inexpressiva, tendência já observada na última década em outras regiões hiperendêmicas. Os autores estão convencidos que o controle da transmissão requer esforços na sentido de melhorar as condições ambientais e que semelhante proposta é inteiramente viável, podendo ser concretizada com o emprego de recursos bastante modestos e contando com a participação da comunidade.